(untitled) (Research, Society and Development, 2020)
The aim of the present study was to verify the profile of the diet offered to newborns admitted to a neonatal intensive care unit. This is a longitudinal, quantitative study with descriptive analysis of the data, developed with newborns admitted to a neonatal intensive care unit located in Rio Grande do Norte-Brazil. The newborns were followed up from a nutritional record that included their general and anthropometric characteristics, as well as information about the diet offered during the hospital stay. 76 NBs were included in the study. Among the main causes of hospitalization were respiratory disorders and prematurity. On the day of admission, the enteral route was the most used to administer food to newborns (63.1%), with the mother’s own pasteurized or milked human milk (57.9%) being offered, and there was no adequate energy intake. by the diet. Subsequently, throughout the hospital stay, it is estimated that there was an adjustment of the energy supply offered to 72.4% of newborns. At this time, the most prevalent route of administration was oral (43.7%), with breast milk being the predominant food (85.5%). At the time of hospital discharge, most NBs were exclusively breastfeeding (65.8%). The dietary evolution aimed at reaching the exclusive breastfeeding by the newborns, favoring the oral route and the energetic-nutritional input necessary for the recovery of patients until hospital discharge. It is suggested that studies be carried out to quantify energy intake through exclusive breastfeeding for an adjusted prediction of energy-nutritional intake by newborns.